Object motion tracking on a cluttered background: a further enhancement of the condensation algorithm - John Paul D. Ang and Johneric Anselmo B. Razon. 4 0 16; 5 (2005)
u
Undergraduate Thesis: (Bachelor of Science in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2